Effect of Lactiplantibacillus plantarum HM-22 on immunoregulation and intestinal microbiota in α-lactalbumin-induced allergic mice. Issue 19 (1st September 2021) - Jiang, Shujuan; Hou, Yaqi; Meng, Lingying; Pu, Xueli; Zhu, Xuemei; Tuo, Yanfeng; Qian, Fang; Mu, Guangqing
Abstract : This work revealed the protective effect of L. plantarum HM-22 in α-LA-induced allergic mice, demonstrated by the alleviation of allergic symptoms, colon inflammation and intestinal microbiota changes. Abstract : Milk protein is one of the eight major allergens, and α-lactalbumin (α-LA) is one of the major allergens of bovine milk protein. Our previous studies found that Lactiplantibacillus plantarum HM-22 ( L. plantarum HM-22) showed a good gastrointestinal survival rate and intestinal colonization. To investigate the effect of L. plantarum HM-22 on intestinal inflammation and intestinal microbiota in α-LA-induced allergic mice, in this study, L. plantarum HM-22 at low and high doses was intragastrically administered to α-LA-induced allergic mice for 5 weeks. The results showed that L. plantarum HM-22 significantly relieved the weight loss and organ index of α-LA-induced allergic mice ( p < 0.05). L. plantarum HM-22 increased the levels of interleukin-10 (IL-10), interferon-γ (IFN-γ) and transforming growth factor-β (TGF-β) in the serum of α-LA-induced allergic mice and decreased the levels of total immunoglobulin E (IgE) and the proinflammatory factor interleukin-4 (IL-4) ( p < 0.05). The crypt structure of the colon tissues of α-LA-induced allergic mice changed, goblet cells decreased, and the phenomenon of a large number of inflammatory corpuscles that appeared was improved and alleviated with the intervention of L. plantarum HM-22 by hematoxylin–eosin (HE) staining. Western blot analysis showed that L. plantarum HM-22 significantly increased the expression of occludin and claudin-1 in the colon of α-LA-induced allergic mice and decreased the expression of the inflammatory proteins p65 and IκBα ( p < 0.05). The intestinal microbiota of mice in each group was determined by 16S rRNA amplicon sequencing, and the results showed that intervention with L. plantarum HM-22 improved the intestinal microbes of α-LA-induced allergic mice. Spearman's correlation analysis revealed the correlation between intestinal microbiota changes and the α-LA-induced allergy-related index. This study provides a theoretical basis for probiotics to prevent allergies by changing the intestinal microbiota.